THE CORRELATION BETWEEN ENVIRONMENTAL AWARENESS AND STUDENTS PARTICIPATION IN GO GREEN SCHOOL ACTIVITY AT ADIWIYATA SCHOOL - Eka Putri Azrai; Diana Vivanti Sigit; Meilani Puji (Universitas Negeri Jakarta, 2017)
Environmental awareness is consciousness of the environment problems for doing positive action through environmental preservation. Environmental preservation is an obligation for every people, including students. Therefore, students participation is needed to preserve school environmental through the Go Green School activity. One of the factors that can affect participation of students in Go Green School activity is their environmental awareness. The study aims to determine the correlation between environmental awareness and participation of students in Go Green School activity at Adiwiyata School. The research was conducted at SMAN 4 Tangerang in April 2016. The method used was survey method with correlational studies. The sample total used was 218 students taken by simple random sampling. Data was normally distributed and homogeneous. The simple regression equation is Ŷ = 44,92 + 0,695X. Correlation coefficient obtained is 0,7566 which means that there is a correlation between environmental awareness with participation of students in Go Green School activity. Environmental awareness of students accounted for 57,24% of the Go Green School activity. The result of this study concluded that there was positive correlation between environmental awareness and participation of students in Go Green School activity.